Interleukin-15 augments oxidative metabolism and fungicidal activity of human monocytes against Paracoccidioides brasiliensis - Bannwart, Camila Ferreira [UNESP] (2010)
Interleukin (IL)-15 is a pleiotropic cytokine that regulates the proliferation and survival of many cell types. IL-15 is produced by monocytes and macrophages against infectious agents and plays a pivotal role in innate and adaptive immune responses. This study analyzed the effect of IL-15 on fungicidal activity, oxidative metabolism and cytokine production by human monocytes challenged in vitro with Paracoccidioides brasiliensis (Pb18), the agent of paracoccidioidomycosis. Peripheral blood monocytes were pre-incubated with IL-15 and then challenged with Pb18. Fungicidal activity was assessed by viable fungi recovery from cultures after plating on brain-heart infusion-agar. Superoxide anion (O2-), hydrogen peroxide (H2O2), tumour necrosis factor-alpha (TNF-α), IL-6, IL-15 and IL-10 production by monocytes were also determined. IL-15 enhanced fungicidal activity against Pb18 in a dose-dependent pattern. This effect was abrogated by addition of anti-IL-15 monoclonal antibody. A significant stimulatory effect of IL-15 on O2- and H2O2 release suggests that fungicidal activity was dependent on the activation of oxidative metabolism. Pre-treatment of monocytes with IL-15 induced significantly higher levels of TNF-α, IL-10 and IL-15 production by cells challenged with the fungus. These results suggest a modulatory effect of IL-15 on pro and anti-inflammatory cytokine production, oxidative metabolism and fungicidal activity of monocytes during Pb18 infection.